The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/jmv.28527
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PIKFYVE kinase interferes ESCRT pathway to suppress RNA virus replication

Abstract: Endosomal sorting complex required for transport (ESCRT) is essential in the functional operation of endosomal transport in envelopment and budding of enveloped RNA viruses. However, in nonenveloped RNA viruses such as enteroviruses of the Picornaviridae family, the precise function of ESCRT pathway in viral replication remains elusive. Here, we initially evaluated that the ESCRT pathway is important for viral replication upon enterovirus 71 (EV71) infection. Furthermore, we discovered that YM201636, a specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Instead, we had reported previously on the observation that phosphoinositides, specifically PI(3,4)P2 are displayed on LPVs [48]. Informed by studies that have identified PI (3,4)P2 and other phosphoinositides as membrane anchors for the recruitment of ESCRT components [42,44] we affirmed that LdLPVs do indeed display PI(3,4)P2, and then observed that treatment with LY294002 led to reduced display of this lipid and also reduced recruitment of CHMP4B to LdLPVs. The experiments with LY294002 were challenging because prolonged incubation of infected cells in this drug (greater than 8hrs) resulted in death of parasites and clearance from infected cells.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Instead, we had reported previously on the observation that phosphoinositides, specifically PI(3,4)P2 are displayed on LPVs [48]. Informed by studies that have identified PI (3,4)P2 and other phosphoinositides as membrane anchors for the recruitment of ESCRT components [42,44] we affirmed that LdLPVs do indeed display PI(3,4)P2, and then observed that treatment with LY294002 led to reduced display of this lipid and also reduced recruitment of CHMP4B to LdLPVs. The experiments with LY294002 were challenging because prolonged incubation of infected cells in this drug (greater than 8hrs) resulted in death of parasites and clearance from infected cells.…”
Section: Discussionsupporting
confidence: 58%
“…There is evidence that some phosphoinositide species are the membrane anchor to which ESCRT components are recruited [42][43][44]. It was shown that for the completion of cytokinesis, phosphoinositides serve as critical membrane anchors for ESCRT molecules ( [10,43].…”
Section: Introductionmentioning
confidence: 99%
“…We also found that inhibitors of host biology, including NAMPT, PIKfyve, and IMPDH, showed activity. PIKfyve inhibitors likely block viral entry ( 21 ). NAMPT inhibitors are very active but have toxicity concerns given their role in cellular energetics.…”
Section: Discussionmentioning
confidence: 99%
“…After Professor Wu set up a lab at Wuhan University, China, he put extensive interests into human medical virology. Professor Wu and his group made fundamental progress in the mechanism of diverse viral infection, replication and pathogenesis, covering most common viruses [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] and viral coinfections [ 17 , 18 , 19 , 20 ] in humans. In addition, Professor Wu devoted himself to mechanism research of viral-induced oncogenesis and exploring virus-based cancer therapeutic strategies.…”
mentioning
confidence: 99%